Digestible energy content of corn and triticale when fed to finishing pigs - Feoli, C.; Monge, C.R.; Gugle, Terry L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Digestible energy content of corn and triticale when fed to finishing pigs
Keywords: Feed ingredients; Triticale; Swine